Effect of ethical leadership and performance evaluation on transfer price prediction: A social learning experiment - Wiharsianti, Ervilia Agustine; Nisa', Fitria Sarifatun (Journal of Accounting and Investment, 2024)
Research aims: This paper investigates two control mechanisms that firms can use to avoid negotiation conflicts in negotiated transfer pricing decisions.Design/Methodology/Approach: This experimental research used a 2x2 factorial design between subjects. This study involved 77 undergraduate economics and business students as participants. Research findings: This result revealed that divisions evaluated with systems that value high ethical leadership and competitive performance evaluation schemes would set transfer prices close to equal profit transfer prices. These results suggest that companies with individual performance evaluations in a decentralized corporate structure can use informal controls such as ethical leadership to manage negotiation conflicts.Theoretical contribution/ Originality: This study provides further knowledge to the ethical leadership literature by examining the influence of ethical leadership and performance evaluation schemes on transfer pricing. Previous research on leadership and transfer pricing prediction is limited and primarily focuses on tone leadership. This research, therefore, develops previous research by focusing on another leadership style, namely ethical leadership, with an experimental design.Practitioner/Policy implication: This research provides an easy and low-cost alternative control mechanism to reduce conflicts that can occur in the transfer price negotiation process.Research limitation/Implication: This research is limited to ethical leadership styles and limited transfer pricing mechanisms. Future research, thus, can use other leadership styles and other transfer pricing mechanisms, such as two-step pricing. Different mechanisms used can produce different decisions as well.